The consequences of the migration crisis on the Balkan route and human rights: The current situation and prospects in Serbia - Magdalena Bogucewicz (Eastern Review, 2020)
This paper reflects on reports documenting human rights violations on the Balkan route as one of the implications of European migration policies, and applies them to the Serbian context. The Republic of Serbia is considered as one of the main transit countries for the migrant traffic on the Balkan Peninsula and eventually has become an unlikely gatekeeper of European Union when many migrants got stranded on its territory as a result of gradual border securitization. Further politics of closed borders have caused a serious concern of non-governmental organizations and activists when violent practices of security forces and smugglers got revealed. Serbia, in its pursuit of EU accession, must prove its respect for fundamental human rights while not losing sight of its national interest.